Development of abemaciclib-encapsulated nanosponges for breast cancer: optimization, drug release kinetics, and in vitro efficacy - Bolledla, Nirosha; Bakshi, Vasudha (Journal of Applied Pharmaceutical Research, 2025)
Background: Abemaciclib (ABC) is a new, orally administered pharmaceutical agent authorised for the purpose of combating breast cancer. The drug's low bioavailability necessitates dosing two to three times daily, which may reduce patient compliance. To lessen the severity of side effects and prolong the duration of action, sustained-release formulations are required. Developing an ABC sustained-release nanoparticle system was the primary goal of this study. Methodology: Both the sustained-release polymer (EC) and the surfactant (KP-188) were derived from ethyl cellulose, in an emulsion-solvent diffusion synthesis of nanosponges (NS). We examined the impact of varying surfactant concentrations and drug-to-polymer ratios on PS, PDI, ZP, %EE, %DL, particle size, drug loading, zeta potential, and polydispersity index. Results and Discussion: The optimized formulation (F11) achieved an entrapment efficiency of 86.52±0.25% and a cumulative drug release of 77.12% over 24 hours. The drug release followed a sustained pattern over 24 hours. It best fits the Higuchi kinetic model, which indicates that drug diffusion was the primary mechanism of release from the matrix system. The MTT experiment demonstrated that ABC might be a viable cytotoxic nanocarrier for breast cancer cells from humans, specifically MCF-7 and MDA-MB-231. On top of that, following contact with storage settings of 25, 5, and 45 °C for six months, ABC maintained its drug release property with no modification in the percentage release. Conclusion: This study shows that the created NS could effectively transport and release ABC, amplifying its impact in the battle against breast cancer.